Hydrodynamic properties of human erythrocyte band 3 solubilized in reduced Triton X-100. - Taylor, A; Boulter, J; Harding, SE; Cölfen, H; Watts, A (1999)
The oligomeric state and function of band 3, purified by sulfhydryl affinity chromatography in reduced Triton X-100, was investigated. Size exclusion high-performance liquid chromatography showed that a homogeneous population of band 3 dimers could be purified from whole erythrocyte membranes. The elution profile of band 3 purified from membranes that had been stripped of its cytoskeleton before solubilization was a broad single peak describing a heterogeneous population of oligomers with a mean Stokes radius of 100 A. Sedimentation velocity ultracentrifugation analysis confirmed particle heterogeneity and further showed monomer/dimer/tetramer equilibrium self-association. Whether the conversion of dimer to the form described by a Stokes radius of 100 A was initiated by removal of cytoskeletal components, alkali-induced changes in band 3 conformation, or alkali-induced loss of copurifying ligands remains unclear. After incubation at 20 degrees C for 24 h, both preparations of band 3 converted to a common form characterized by a mean Stokes radius of 114 A. This form of the protein, examined by equilibrium sedimentation ultracentrifugation, is able to self-associate reversibly, and the self-association can be described by a dimer/tetramer/hexamer model, although the presence of higher oligomers cannot be discounted. The ability of the different forms of the protein to bind stilbene disulfonates revealed that the dimer had the highest inhibitor binding affinity, and the form characterized by a mean Stokes radius of 114 A to have the lowest.